Analysis of wave measurements in November 2018, January 2019, and March 2019 in the coastal waters of Leupung and Lhoong, Aceh Besar District, Indonesia. Issue 1 (February 2021) - Setiawan, I; Yuni, S M; Purnawan, S; Isman, R S; Miftahuddin, M; Ilhamsyah, Y
Abstract: The coastal waters of Leupung and Lhoong Aceh Besar District are directly adjacent to the Indian Ocean. They play a major role in fishing and tourism activities. Thus, the study of ocean waves is important to conduct. The research aims to describe the variations of waves, i.e., height and period. The research was carried out in Leupung at station 1 and Lhoong at station 2 in November 2018, January 2019, and March 2019. The height and period of the waves were collected from 2 station points located at Leupung and Lhoong beaches, using the direct measurement method, that is, a scale meter to measure the wave height and a stopwatch to measure the wave period before the breaking wave. The results show that the wave height and period in November 2018, January 2019, and March 2019 in Leupung coastal waters are 0.42 m, 12.34 s; 0.5m, 12.43 s; 0.49 m, 13.82 s, respectively. Meanwhile, wave height and period in Lhoong coastal waters are 0.26 m, 12.31 s; 0.44 m, 13.97 s; 0.48 m, 12.22 s, respectively. It is concluded that the highest wave occurred in January and March 2019 at Leupung and Lhoong coastal waters, respectively. On average, the highest wave of the three months occurred in Leupung coastal waters.